Energy Utilization of Torrefied Residue from Wine Production - Tamelová, Barbora; Malaťák, Jan; Velebil, Jan; Gendek, Arkadiusz; Aniszewska, Monika (Materials (Basel, Switzerland), 2021)
A significant amount of waste is generated in the food industry, which is both an environmental and an economic problem. The recycling of this waste has become an important area of research. The processing of grapes produces 20-30% of the waste in the form of grape pomace and stalks. This article assesses the fuel values of these materials before and after torrefaction. The input materials were grape pomace samples from the varieties Riesling (Vitis vinifera "Welschriesling") and Cabernet Sauvignon (Vitis vinifera "Cabernet Sauvignon") from the South Moravia region and stalks from the variety Welschriesling. The torrefaction process was performed using a LECO TGA 701 thermogravimetric analyzer under nitrogen atmosphere at set temperatures of 225 °C, 250 °C, and 275 °C. The residence time was 30 min. Elemental analysis, calorific value, and gross calorific value were determined for all samples. The analyses show a positive effect of torrefaction on fuel properties in the samples. Between temperatures 250 °C and 275 °C, the carbon content increased by 4.29 wt.%, and the calorific value increased with the increase in temperature reaching a value of 25.84 MJ·kg-1 at a peak temperature of 275 °C in the sample grape pomace from blue grapevine.
Keywords: elemental analysis; biochar; energy properties; bioenergy; torrefaction